Germ-Free Mice Under Two-Layer Textiles Are Fully Protected From Bacteria in Sprayed Microdroplets: A Functional in vivo Test Method of Facemask/Filtration Materials - Rodriguez-Palacios, Alex; Conger, Mathew; Cominelli, Fabio (Frontiers in Medicine, 2020)
Several studies have measured the effectiveness of masks at retaining particles of various sizes in vitro. To identify a functional in vivo model, herein we used germ-free (GF) mice to test the effectiveness of textiles as droplet barriers to complement available in vitro-based knowledge. Herein, we report a study conducted in vivo, to determine to what extent household textiles prevent contamination of GF mice in their environment, with bacteria-carrying microdroplets. Using a recently validated spray-simulation method (mimicking a sneeze), herein we first determined that combed-cotton textiles used as 2-layer-barriers covering the mouse cages, prevented the contamination of all GF animals when sprayed 10-20 bacterial-droplet units/cm2. In additional exposure trials, the model showed that GF mice were again protected by the combed-cotton textile after the acute exposure to 10-times more droplets (20 ‘spray-sneezes’). Overall, 2-layer combed-cotton protected 100% of the GF mice from bacteria-carrying droplets (n=20 exposure-events), which was significantly superior, compared to 100% mouse contamination without textile coverage, or when 95%-partly-covered (n=18, Fisher-exact, p<0.0001). Of relevance, two different densities of cotton were equally effective (100%) in preventing contamination, regardless of density (120-vs-200g/m2; T-test, p=0.0028), suggesting that similar density materials could prevent droplet contamination. As a practical message, we conducted a speech trial (counting numbers, 1-to-100) with/without the protection of the same cotton textile used as facecover. The trial illustrated that contamination of surfaces occurs at a rate of >2-6 bacteria-carrying saliva-droplets per word (2.6 droplets/cm2, 30cm) when speaking at 60-70 decibels, and that cotton facecovers fully prevent bacterial surface contamination.